Peran Acta Van Dading Sebagai Penyelesaian Sengketa: Studi Kasus Wanprestasi Dalam Kontrak Kemitraan Sawit - Tobing, Vania Athalia Lumban; Manalu, Yuris Utrecht Boantua; Fatin, Kayla Alima; Prakosa, Reza Bintang; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The resolution of disputes in cases of breach of contract (wanprestasi) can be amicably achieved through acta van dading. A peace agreement through acta van dading involves both parties agreeing to fulfill their rights and obligations as outlined in the mutual agreement. This study focuses on a case study of breach of contract in a palm oil partnership involving PT. AD against PT. SS and PT. AB under Case Number 36/Pdt.G/2024/PN Pkb, which was resolved amicably through acta van dading. Based on this, the authors conducted research to determine whether the actions of PT. AD can be categorized as a breach of contract from a legal perspective and how the dispute was resolved through acta van dading. The research method used is qualitative, with a normative juridical approach. This approach examines legal regulations and theories related to acta van dading in resolving breach of contract disputes in palm oil partnership agreements. The findings of this study demonstrate that acta van dading is effective in resolving breach of contract disputes as it preserves business relationships between parties. However, the success of the resolution heavily depends on the compliance of the parties with the terms of the agreement. This research provides insights into the application of the breach of contract concept and the effectiveness of acta van Dading as a solution for resolving disputes in business contracts.